An atypical GdpP enzyme linking cyclic nucleotide metabolism to osmotic tolerance and gene regulation in Mycoplasma bovis - Zhu, Xifang; Baranowski, Eric; Hao, Zhiyu; Li, Xixi; Zhao, Gang; Dong, Yaqi; Chen, Yingyu; Hu, Changmin; Chen, Huanchun; Citti, Christine; Wang, Aiping; Guo, Aizhen (Frontiers in Microbiology, 2023)
Nucleotide second messengers play an important role in bacterial adaptation to environmental changes. Recent evidence suggests that some of these regulatory molecular pathways were conserved upon the degenerative evolution of the wall-less mycoplasmas. We have recently reported the occurrence of a phosphodiesterase (PDE) in the ruminant pathogen Mycoplasma bovis, which was involved in c-di-AMP metabolism. In the present study, we demonstrate that the genome of this mycoplasma species encodes a PDE of the GdpP family with atypical DHH domains.Characterization of M. bovis GdpP (MbovGdpP) revealed a multifunctional PDE with unusual nanoRNase and single-stranded DNase activities. The alarmone ppGpp was found unable to inhibit cdi-NMP degradation by MbovGdpP but efficiently blocked its nanoRNase activity. Remarkably, MbovGdpP was found critical for the osmotic tolerance of M. bovis under K + and Na + conditions. Transcriptomic analyses further revealed the biological importance of MbovGdpP in tRNA biosynthesis, pyruvate metabolism, and several steps in genetic information processing. This study is an important step in understanding the role of PDE and nucleotide second messengers in the biology of a minimal bacterial pathogen.